Developmental progression in performance evaluations: Effects of children's cue-utilization and self-protection. (October 2017) - van Loon, Mariëtte; Destan, Nesrin; Spiess, Manuela A.; de Bruin, Anique; Roebers, Claudia M.
Abstract: To effectively self-regulate learning, children need to self-evaluate whether they meet learning goals. Unfortunately, self-evaluations are often inaccurate, typically, children are overconfident. We investigated two explanations for developmental progression in self-evaluations related to children's (48 5/6-year-olds and 53 7/8-year-olds) interpretations of performance: Improved reliance on item difficulty, and reduced sensitivity to self-protection biases. Self-evaluations were more accurate for 7/8-year-olds than for 5/6-year-olds. There was no developmental increase in reliance on item difficulty; even 5/6-year-olds made adaptive use of this cue. Both age groups were overconfident for incorrect responses, but were able to use performance feedback to improve confidence judgments. However, when self-rewarding, 5/6-year-olds were less likely to take negative performance feedback into account than 7/8-year-olds. The 5/6-year-olds were able to base confidence judgments on performance feedback, but did not use feedback to the same extent when self-rewarding. This may indicate that self-protective biases are an important cause of overconfidence in children. Highlights: For effective self-regulation, children must accurately self-evaluate performance. The 5/6-year-old children are more overconfident than 7/8-year-old children. Both age groups base self-evaluations on item difficulty and performance feedback. The 5/6-year-olds gave inappropriately high self-reward for incorrect performance. Self-protective biases seem an important cause of inaccurate self-evaluations.